Corporate governance and dividend pay-out policy in UK listed SMEs - Mohamed Elmagrhi (International Journal of Accounting & Information Management, 2017)
Purpose: This paper examines the extent to which corporate board characteristics influencethe level of dividend pay-out ratio using a sample of UK small and medium-sized enterprises(SMEs) from 2010 to 2013 listed on the Alternative Investment Market.Design/methodology/approach: The data is analysed by employing multivariate regressiontechniques, including estimating fixed effects, lagged effects and two-stage least squaresregressions.Findings: The results show that board size, the frequency of board meetings, board genderdiversity and audit committee size have a significant relationship with the level of dividendpay-out. Audit committee size and board size have a positive association with the level ofdividend pay-out, whilst the frequency of board meetings and board gender diversity has asignificant negative relationship with the level of dividend pay-out. By contrast, the findingssuggest that board independence and CEO role duality do not have any significant effect onthe level of dividend pay-out.Originality/value: This is one of the first attempts at examining the relationship betweencorporate governance and dividend policy in the UK’s Alternative Investment Market, with theanalysis distinctively informed by agency theoretical insights drawn from the outcome andsubstitution hypotheses.